Measuring Unfinished Nursing Care: What to Consider When Choosing and Scoring Surveys. Issue 1 (January 2016) - Jones, Terry L.; Gemeinhardt, Gretchen; Thompson, Julia A.; Hamilton, Patti
Abstract : Unfinished nursing care is common in the inpatient setting and is associated with negative patient outcomes. This indicator is being assessed with increasing frequency to determine the quality of nursing services. Measurement bias was identified in this comparison of unfinished care surveys. Potential sources of bias should be considered when selecting and scoring unfinished nursing care surveys for quality assessment. Abstract : Supplemental Digital Content is Available in the Text.